Reassessment of morphological diagnostic characters and species boundaries requires taxonomical changes for the genus orthopyxis L. Agassiz, 1862 (campanulariidae, hydrozoa) and some related campanulariids. - Amanda F Cunha; Gabriel N Genzano; Antonio C Marques (PLoS ONE)
The genus Orthopyxis is widely known for its morphological variability, making species identification particularly difficult. A number of nominal species have been recorded in the southwestern Atlantic, although most of these records are doubtful. The goal of this study was to infer species boundaries in the genus Orthopyxis from the southwestern Atlantic using an integrative approach. Intergeneric limits were also tested using comparisons with specimens of the genus Campanularia. We performed DNA analyses using the mitochondrial genes 16S and COI and the nuclear ITS1 and ITS2 regions. Orthopyxis was monophyletic in maximum likelihood analyses using the combined dataset and in analyses with 16S alone. Four lineages of Orthopyxis were retrieved for all analyses, corresponding morphologically to the species Orthopyxis sargassicola (previously known in the area), Orthopyxis crenata (first recorded for the southwestern Atlantic), Orthopyxis caliculata (= Orthopyxis minuta Vannucci, 1949 and considered a synonym of O. integra by some authors), and Orthopyxis mianzani sp. nov. A re-evaluation of the traditional morphological diagnostic characters, guided by our molecular analyses, revealed that O. integra does not occur in the study area, and O. caliculata is the correct identification of one of the lineages occurring in this region, corroborating the validity of that species. Orthopyxis mianzani sp. nov. resembles O. caliculata with respect to gonothecae morphology and a smooth hydrothecae rim, although it shows significant differences for other characters, such as perisarc thickness, which has traditionally been thought to have wide intraspecific variation. The species O. sargassicola is morphologically similar to O. crenata, although they differ in gonothecae morphology, and these species can only be reliably identified when this structure is present.